Epiphytiology of charcoal rot caused by Macrophomina phaseolina in soybean fertilized with biol and biosol (Bioagro, 2021)
The pathogenic fungus Macrophomina phaseolina, which causes charcoal rot, attacks important plant species, and measures have been proposed for its control through the application of organic amendments. The objective of this research was to evaluate the effect of Biol and biosol organic fertilizers, by soil and foliar application in soybean ʽCigras 06 ʼ (Glycine max), on the epiphytiology of the disease. The test was established under water stress and high solar radiation conditions. A total of 15 treatments were applied that represented four types of fertilization management: conventional (urea+NPK), edaphic biosol, edaphic biol, and foliar biol. Soil fertilization with balanced biol and biosol was calculated according to the principles of cationic balance in soil solution. Foliar fertilization with corrected biol was made by pH neutralization. The results were analyzed by ANOVA and Tukey test. To define the behavior of the epiphytia, trend curves were constructed from the calculation of area under disease progress curve (AUDCP) based on accumulated mortality. Regression equations and risk coefficients were obtained in each treatment. A correlation matrix was built between standardized data by principal components analysis PCA. Charcoal rot followed an exponential model characteristic of monocyclic epiphytes. The disease critical period ranged from V4 to R1, where the bulk of mortality occurred reaching 75% in the control without fertilizers. The application of biosol with urea made it possible to counteract the effects of the pathogen at 66,75 %.
Keywords: Edaphic and foliar fertilization; Glycine max; plant pathology